2021
DOI: 10.1080/23311975.2021.1892256
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing consumers’ self-reported loyalty intentions in Islamic Banks: The relationship between service quality and the mediating role of customer satisfaction

Abstract: The main objective of this paper is to investigate how service quality and customer satisfaction are correlated to self-reported loyalty intentions in Islamic banks. The paper presents primary data collected by self-administered questionnaires involving a sample of 655 respondents from all local Islamic Banks in Jordan. The results show that compliance, tangibility, responsiveness, assurance, and empathy positively linked to self-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 108 publications
6
44
1
1
Order By: Relevance
“…However, the results show that functional and TQ were not significant ( p > 0.05), indicating no mediation effect with satisfaction. This finding of the current study is not consistent with past studies (Dandis et al , 2021b; Dandis and Wright, 2020; Al-dweeri et al , 2019; Ahmadi, 2019), which reported customer satisfaction to be a mediating factor between service quality dimensions and attitudinal or behavioural loyalty. For example, Ahmadi (2019, p. 53) found “all dimensions of service quality have the significant indirect effect on word of mouth (mediated through customer satisfaction)”.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the results show that functional and TQ were not significant ( p > 0.05), indicating no mediation effect with satisfaction. This finding of the current study is not consistent with past studies (Dandis et al , 2021b; Dandis and Wright, 2020; Al-dweeri et al , 2019; Ahmadi, 2019), which reported customer satisfaction to be a mediating factor between service quality dimensions and attitudinal or behavioural loyalty. For example, Ahmadi (2019, p. 53) found “all dimensions of service quality have the significant indirect effect on word of mouth (mediated through customer satisfaction)”.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, “most studies measure loyalty as a single component rather than a separate component consisting of WOM, WPM, and RI” (Ong et al , 2018, p. 758). Consequently, this study adopted true brand loyalty (attitudinal and behavioural loyalty) to be measured CLV, whereas most earlier studies (Dandis and Wright, 2020; Dandis et al , 2021b) take one dimension to represent the loyalty construct. Particularly, a customer's true loyalty was measured in terms of separate factors of RI, WPM and WOM to expand our thoughtful of both theoretical and management interest (Ong et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for higher quality products and better customer services along with lower prices is creating an intense competition between rivals. Therefore, companies found themselves forced to understand customers' requests and respond to them (Dandis et al, 2021), which leads to establishing better relationships with customers (Shukla & Pattnaik, 2019). Accordingly, maintaining this relationship is a major priority.…”
Section: Introductionmentioning
confidence: 99%
“…Por consiguiente, las principales preocupaciones de las organizaciones son las dimensiones de la calidad del servicio, la satisfacción y la fidelidad. (Dandis et al, 2021); es así como, el objetivo de la presente investigación es indagar la influencia de la calidad del servicio percibida sobre la fidelización del cliente y el carácter mediador de la imagen de marca sobre dicha relación, en las principales cadenas de moda textil que operan en el Ecuador.…”
unclassified